DIAPIR FORMATION IN THE ZONE OF KANIV DISLOCATIONS: GEOLOGICAL AGE, FACTORS AND PALEOGEOGRAPHIC CONDITIONS - Popova, L.; Prysiazhniuk, V.; Kovalchuk, O.; Тustanovska L. (Visnyk of Taras Shevchenko National University of Kyiv. Geology, 2025)
The Melanchyn Potik gully (the southern part of the Kaniv dislocations) cuts several folds of the north-north-west dipping. Cores of these folds are composed by the Callovian clay. Today, against the background of the overall decreasing of exposed areas, the Melanchyn Potik is a unique possibility to juxtapose geological structures, biostratigraphic data and geometrical morphometric data. In order to do that, a large-scale thrust-faulted diapiric fold has been studied in the middle reaches of this gully. Geological structure of the Quaternary deposits on its limbs is evidenced that large-scaled thrustfaulted deformations were followed by active slope-wash processes in the absence of a developed fluvial network. It led to the accumulation of the slopewash deposits at sight, on the neighboring slopes and in depressions. Sometimes deposition in the synclines was rhythmic, probably due to seasonal changes in the flow velocity (spring/summer). Apart from these recurrent (seasonal) changes, sedimentation alternated with non-periodical events, supposedly, repeated dislocations of smaller scale. Thus, two levels of superposed deformation are observed on the back-limb of the thrust-faulted diapiric fold. These deformations are supposed to be contemporary with slope-wash accumulation on the limbs. The Quaternary deposits of the studied area show features of the single depositional cycle that probably corresponded to a rather short chronological interval. This reconstruction is supported by the composition of the fossil fauna. Fossils were collected layerwise from the filling of the fore-limb inter-scale depression (the taphocoenosis of Melanchyn Potik 1) and from the slope-wash deposits of the back-limb of the thrust-fault disturbed by the secondary deformations (the taphocoenosis of Melanchyn Potik 2). Numerous landsnails and scarce remains of amphibians and small mammals have been obtained. Both taphocoenoses generally support the picture of young severe landscape with water-flooded lowlands and drier plots of more xerphitic vegetation on hills. Changes of the composition of the gastropod fauna upward the sections are explained by dynamics of the surface wash rather than the climatic factor. Possible age of the deposits determined by the composition of rodent remains range from the second half of the Middle Pleistocene to the end of the Late Pleistocene. However, proceeding from the aforesaid, this interval should be restricted to the time of the Dnieper glaciation. Overall fauna (both gastropods and mammals) is rather cold tolerant, but not being extremely cryophilic. Both the faunal composition and the type of the secondary deformations indicate the absence of the gapless permafrost distribution. A new clue to the paleogeographic reconstruction of the Dnieper period is brought by the findings of amphibians. Their remains in the Dnieper deposits emphasize that the analogy between landscape and climatic conditions of recent near-glacier areas and those of the Dnieper glaciation is untenable. If to consider the Melanchyn Potik gully as a model in miniature for the Kaniv dislocations, the scenario of the dislocation will correspond to that proposed by A.V. Matoshko, Yu.G. Chugunnyi. Namely, structures of the thrust-faulted allochthon preceded the formation of the Injective Swell and, alongside with other factors, controlled further dislocations. Water that squashed from under the glacier moved laterally because Jurassic clay in the basis of the upper structural storey of the allochthone having been squashed and stretched in the course of thrust-fault movement formed an upper confining layer. At the boundaries between main structures, this water outpoured to the large bulk of porous deposits (Cretaceous, Paleogene, Quaternary alluvial ones) and saturated them. The pressure on underlying deposits increased and the belt of secondary protrusions and diapirs (Injective Swell) was formed. Data of the geometrical morphometry, on the contrary, are evidence of the scenario proposed by Yu.A. Lavrushyn, Yu.G. Chugunnyi (the Injective Swell preceded the thrust-faulted allochthon).